Nigeria and the oil question : presidential address delivered at the annual conference of the Nigerian Economic Society, Lagos, February 1979 - Asiodu, Philip C. ([Lagos] : The Society, 1979)
This paper addresses various questions on oil related issue and it drawbacks to national development.
asm; 26/04/19
Loans
Keywords: Petroleum industry and trade; Nigeria